PERBEDAAN HASIL TATA RIAS PESTA PADA WANITA DEWASA PENGGUNA SKINCARE DENGAN MENGGUNAKAN BEBERAPA JENIS FOUNDATION - Putri Ardani, Emillya; M.A. Hanny Ferry Fernanda; Dewi Lutfiati; Sri Usodoningtyas (Program Studi Pendidikan Tata Rias, 2024)
Party makeup aims to enhance facial beauty and conceal skin imperfections, particularly for adult women who regularly use skincare products. This study aims to: 1) evaluate the results of party makeup on adult female skincare users using liquid, cream, and stick Foundations based on the indicators of evenness, smoothness, and durability; and 2) identify the differences in makeup outcomes among the three types of Foundations. The research employs a quantitative approach with a factorial experimental design, conducted through the observation of Foundation application at the PKK Makeup Laboratory, Faculty of Engineering UNESA. The findings indicate that cream Foundation excels in smoothness, providing a natural appearance and effectively concealing pores. Liquid Foundation demonstrates the best durability, making it suitable for long-lasting makeup. Stick Foundation also offers good durability but is slightly less even compared to the other types. The analysis concludes that cream Foundation is the optimal choice as it performs excellently in evenness, smoothness, and durability. Liquid Foundation is recommended for events requiring high durability, although improvements in evenness and smoothness are needed. Stick Foundation is suitable for aesthetic results but has shortcomings in evenness and smoothness. Overall, cream Foundation is the preferred option for optimal party makeup results.